2019
DOI: 10.1002/jcp.28519
|View full text |Cite
|
Sign up to set email alerts
|

Disease mechanisms and neuroprotection by tauroursodeoxycholic acid in Rpgr knockout mice

Abstract: Mutations in the retinitis pigmentosa GTPase regulator (RPGR) gene are the predominant cause of retinitis pigmentosa. RPGR plays a critical role as a scaffold protein in the regulation of protein trafficking from the basal body to the axoneme, where the cargoes are transported to the outer segments (OSs) of photoreceptors. This trafficking process is controlled directly by intraflagellar transport complexes and regulated by the RPGR protein complex, although the precise mechanisms have yet to be defined. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…In inherited retinal degeneration (retinitis pigmentosa, RP), TUDCA prevented photoreceptor degeneration in rpgr knockout mice, an RP mouse model. TUDCA also ameliorated microglial activation and infiltration to the photoreceptor layer [ 14 ]. Activated microglia can produce proinflammatory cytokines, e.g., IL-1β and TNF-α, and TUDCA treatment suppressed inflammasome formation and decreased IL-1β production in the rpgr knockout mouse retinas [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In inherited retinal degeneration (retinitis pigmentosa, RP), TUDCA prevented photoreceptor degeneration in rpgr knockout mice, an RP mouse model. TUDCA also ameliorated microglial activation and infiltration to the photoreceptor layer [ 14 ]. Activated microglia can produce proinflammatory cytokines, e.g., IL-1β and TNF-α, and TUDCA treatment suppressed inflammasome formation and decreased IL-1β production in the rpgr knockout mouse retinas [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have examined the protective effect of TUDCA against photoreceptor degeneration in a retinitis pigmentosa GTPase regulator ( Rpgr ) knockout mouse model of retinitis pigmentosa. We found that TUDCA attenuated caspase-dependent photoreceptor cell death, inhibited retinal microglial activation, and suppressed inflammasome formation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…RPGR plays a vital role as a scaffold protein in the regulation of protein trafficking, thus the cargoes can be transported to the outer segments (OSs) of photoreceptors. This trafficking process is controlled by intraflagellar transport complexes and regulated by the RPGR protein complex [29]. The C-terminus of RPGR that contains prenylated site can interact with PDE6δ, INPP5E, and RPGRIP1L, thus regulates ciliary localization of INPP5E [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…But further study should perform to validate the hypothesis in the future. Tauroursodeoxycholic acid (TUDCA) has demonstrated therapeutic potential for RPGR patients by suppressing microglial activation and inflammation and preventing photoreceptor degeneration in Rpgr conditional knockout mice [29]. Adeno-associated viral (AAV) vectors were conducted for RPGR gene therapy by targeting gene expression to both rods and cones in non-human primates [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of nephrocystin-4 (NPHP4), a component of the RPGR unit, was also absent in connecting cilium along with scaffold protein NOD-like receptor family pyrin domain containing receptor 3 (NLRP3) colocalization with microglial neuroinflammation marker ionized calcium binding adaptor molecule 1 (IBA1) in early stages of RPGR knockout mice morphology, a potential contributor to degeneration. Treatment with TUDCA significantly attenuated photoreceptor loss when compared to untreated knockout mice and significantly reduced microglia activation, mimicking morphological similarities to the wild type group [ 114 ]. Lastly, an in vitro model of AMD using retinal pigment epithelial and choroid endothelial cells; TCA treatment maintained tight junction structure and function affected by AMD-induced oxidative stress and inhibited choroidal angiogenesis [ 115 ].…”
Section: Bile Acids In Neurodegenerative Diseasesmentioning
confidence: 99%